Impedance Testing in Esophageal Atresia Patients - Hassan, Maheen; Mousa, Hayat (Frontiers in Pediatrics, 2017)
Esophageal atresia patients are predisposed to gastroesophageal reflux as a result of the altered esophageal anatomy and motility. These patients experience significant morbidity from gastroesophageal reflux. As a result, an effective way to diagnose and monitor for reflux is crucial. pH-metry is able to quantify acid burden, ensure that acid suppression is adequate during long-term follow-up, and correlate acid reflux to symptoms. pH with impedance is additionally able to detect non-acid reflux as well as volume clearance, both of which also correlate with patient symptoms. It is also able to correlate extra-gastrointestinal symptoms to reflux, which may help guide treatment. If complications associated with uncontrolled reflux are identified, aggressive reflux management is necessary, oftentimes requiring surgical intervention.